The association between unilateral and bilateral performance-related measures in elite female soccer players: a multifaceted investigation - Paravlic, Armin Huso; Abazovic, Ensar; Milanović, Zoran; Vučković, Goran; Spudić, Darjan; Hadzic, Vedran; Pajek, Maja; Vodičar, Janez (Frontiers in Physiology, 2024)
Purpose: The present study aimed to investigate a) the associations between bilateral performance utilizing countermovement jump (CMJ), squat jump (SJ), speed and unilateral CMJ, isokinetic peak torque in knee extension and flexion with angular velocities of 60°/s and 180°/s and tensiomyography parameters; b) whether the asymmetries derived from unilateral tests are associated with bilateral CMJ, SJ and MRS in elite female soccer players. Methods:Thirty-five elite female soccer players (average age: 20 ± 5 years) completed CMJ, SJ, speed, isokinetic muscle strength and TMG tests. Results: Compared to the non-dominant leg, the dominant leg demonstrated greater peak torque output in both knee flexion (7.4%) and knee extension (5.6%) isokinetic tasks, as well as m. vastus medialis contraction time (7.6%), and soccer-specific agility test (4.1%). Conversely, the H:Q peak torque ratio at 180º/s (8.5%) was significantly greater in the non-dominant leg. The associations between CMJ, SJ and speed performance ranged from weak (r = 0.350) to large (r = 0.649). For speed, correlations ranged from slightly moderate (r = -0.345, p = 0.042, for vastus medialis contraction time) to large (r = -0.530, p = 0.001, for biceps femoris contraction time). Conclusions: The overall significant, albeit inconsistent, correlations between the diverse performance scores obtained highlight the necessity for a multifaceted and thorough diagnostic strategy in female soccer players.